2011
DOI: 10.1186/1471-2474-12-137
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided versus blind corticosteroid injections in adults with shoulder pain: A systematic review

Abstract: BackgroundCorticosteroid injections can be performed blind (landmark-guided) or with image guidance, and this may account for variable clinical outcomes. The objective of this study was to assess the effectiveness and safety of image-guided versus blind corticosteroid injections in improving pain and function among adults with shoulder pain.MethodsMEDLINE, the Cochrane Controlled Trials Register and EMBASE were searched to May 2010. Additional studies were identified by searching bibliographies of shortlisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 17 publications
0
68
0
Order By: Relevance
“…Furthermore, no difference was detected at first entry in fluoroscopic injection Many studies indicate that superior and earlier improvement in shoulder pain and increased range of motion in the shoulder joint are possible with US-guided injections compared to blind injections. [2,5,14] In our study, clinically improved pain was observed in all patients except one. Decrease in VAS scores continued for one month.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Furthermore, no difference was detected at first entry in fluoroscopic injection Many studies indicate that superior and earlier improvement in shoulder pain and increased range of motion in the shoulder joint are possible with US-guided injections compared to blind injections. [2,5,14] In our study, clinically improved pain was observed in all patients except one. Decrease in VAS scores continued for one month.…”
Section: Discussionmentioning
confidence: 69%
“…[1] Intra-articular injections are widely used to treat shoulder pain and can be administered blindly using anatomical or imaging guidance techniques such as ultrasound (US) or fluoroscopy (FL). [2,3] In daily practice, most of the intra-articular injections have been performed blindly for many years. However, performing the injections to the wrong place may reduce the effectiveness of treatment.…”
mentioning
confidence: 99%
“…The data are conflicting whether this translates into improved clinical efficacy [9,[14][15][16]. Cost-effectiveness has also become an essential part of the equation when assessing the clinical utility of procedures and tests.…”
Section: Indications and Specifications For Ultrasound Guided Proceduresmentioning
confidence: 99%
“…US-guided shoulder injections appear to have a higher percentage of success, more effective analgesia and better functional recovery 6 weeks after injection [54,55].…”
Section: • Shoulder Jointmentioning
confidence: 99%